WOMEN ENTREPRENEURSHIP THROUGH PATTACHITRA AND THEIR SUSTAINABILITY IN RURAL AREAS WITH SPECIAL REFERENCE TO RAGHURAJPUR - Mishra, Madhubrata; Pattanaik, Sasmita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India obtains a recognition in world scenario due to its wealthy artistic, cultural background through its historic art and crafts. These historic art and crafts now reputedly have a prominent prospect in the global market due to their customary beauty, delicacy and legitimacy. Among all the art and crafts of India, Pattachitra of Raghurajpur, Odisha inhabited an eminent place due to its novelty, creative patterns, designs and depictions of simple ideas, usually mythological description. Earlier this artwork was confined only in Odisha and used in the devoted purposes of lord Jagannath. But at present due to new marketing technologies this artwork has outstretched each and every corner of the globe and generated a noticeable source of income for the country. The present study on, “Women Entrepreneurship through Pattachitra and their sustainability in rural areas with special reference to Raghurajpur”, is carried on in the coastal districts of Odisha focusing mainly in the village Raghurajpur. Field data were collected from 25 rural women entrepreneurs through survey cum personal interview taking into consideration their socio-economic condition, business dimension and employment opportunities created by them, problems faced, and promotional strategies adopted by them. The outcome reveals that rural women entrepreneurs play an indispensable role not only in the publicity of this rare artwork all around the globe but also furnish a lot for the whole upliftment of socio-economic situations of the rural crafts women.